Kyai's Charismatic Leadership in Shaping Students Personality at Islamic Boarding Schools - Lalu Abdurrahman; Afiful Ikhwan; Aldo Redho Syam (Edukasia Islamika : Jurnal Pendidikan Islam, 2022)
Islamic boarding schools are present as a forum for education and the formation of a complete Muslim personality, as well as being one of the solutions to produce a generation that has a good personality attitude. Charismatic behavior in Islamic boarding schools is very important in order to maintain and improve Islamic values as a whole. Therefore, the purpose of this study is to describe the process of personality formation and the role of charismatic kyai in Islamic boarding schools. The method used is a qualitative approach that aims to describe the phenomena that exist in the field using written and spoken words from the behavior and people observed, data collection techniques through observations, interviews and documentation, validity check techniques data by increasing persistence, data triangulation and auditing. The results of this study are Islamic boarding schools in shaping the students personality through three processes, namely; learning, supervision and sanctions, while the leadership role of the charismatic kyai is seen from his position as a leader, teacher, policy maker, controller and advisor, and seen from his role as uswah hasanah or role model, has a high caring attitude and is always social.